2005
DOI: 10.1055/s-2005-871773
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 360° Pedicle Torsion on Island Skin Flaps: Experimental Study in Rats

Abstract: This study was carried out to observe the isolated effects of pedicle torsion on island skin flaps, without further damaging the pedicle. Twelve adult male Sprague-Dawley rats, weighting 240 to 300 gr, were used, and hexagonal flaps with edges measuring 1.5 cm and pedicles measuring 1 cm in length were raised in the inguinal region. The animals were divided into two groups. In Group A, flaps were re-sutured to the donor beds without any rotation. In Group B, flaps were rotated 360 degrees, applying the same de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…This finding accounted for the majority of venous congestion versus reduced arterial inflow we found in our series. Experimental experience [8] seems to suggest that a rotation of as much as 360°does not affect the patency of the vessels, providing that the pedicle is dissected extensively and free from all potential constrictions. It also has been stated that pedicle length is inversely proportional to the critical angle of twisting [22,26], suggesting, the longer the pedicle is, the wider a safe arc of rotation will be ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This finding accounted for the majority of venous congestion versus reduced arterial inflow we found in our series. Experimental experience [8] seems to suggest that a rotation of as much as 360°does not affect the patency of the vessels, providing that the pedicle is dissected extensively and free from all potential constrictions. It also has been stated that pedicle length is inversely proportional to the critical angle of twisting [22,26], suggesting, the longer the pedicle is, the wider a safe arc of rotation will be ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Skin flap necrosis could be attributable to insufficient arterial blood flow, but poor venous outflow may also be responsible for inadequate perfusion and consequent flap failure. 15,16 Because of the thinner wall, lower elasticity, and lower pressure in the venous system, the effects of twisting applied to the veins of the pedicle are more evident, resulting in venous insufficiency and consequent flap congestion. 17 However, there are other factors that affect flaps viability, and blood viscosity represents a key element of flap blood flow regulation.…”
Section: Discussionmentioning
confidence: 98%
“…6,7,[24][25][26] These effects have been investigated separately in flaps with axial patterned and perforator flaps, and torsion has also been shown to disrupt flap circulation through similar mechanisms. [3][4][5] Although, on the basis of clinical experience, it may be suggested that perforator flaps are more sensitive to the harmful effects of pedicle rotation, no studies comparing the durability of axial patterned and perforator flaps with pedicle rotation have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The groin flap is supplied by the superficial epigastric artery and has been used in previous similar studies. 3,4 The posterior thigh flap possesses a musculocutaneous perforator vessel. Although this artery is small, it is not difficult to isolate with meticulous dissection, and the most important advantage over other perforator flap models is that two posterior thigh perforator-based flaps are available per animal.…”
Section: Discussionmentioning
confidence: 99%